PERANCANGAN SISTEM INFORMASI TRACKING SURAT KEPENDUDUKAN PADA KANTOR DESA SUKAMANAH BERBASIS WEBSITE - Ahmad Hirzi (2021)
The research conducted this time was to build an information system for tracking population letter submitted by the community at the Sukamanah Village office. Village office employees still have problems finding letters, one of which is a population letter. In the current manual tracking system there is a risk of searching for old mail development paths or losing data stored in hardcopy letter files. The manual tracking system makes public service less optimal. The purpose of doing this research is to be able to produce an information system that is useful in knowing the flow of the existence of letters submitted by the public in streamlining time and knowing the progress of a web-based letter submission. The waterfall method was chosen as the development method used in this study so that it can provide output in the form of a website that is able to make it easier for employees to track population letter submitted by the local community. With the formation of a population letter tracking information system in Sukamanah Village from this research, it is hoped that it can facilitate the Sukamanah Village office employees in serving population letter.